Assessing the Quality of Life of Dental Students by using the WHOQOL-BREF Scale - Burdurlu Muammer Cagri; Cabbar Fatih; Dagasan Volkan; Kulle Cinar; Ozenen Didem Ozdemir; Tomruk Ceyda Ozcakir (Balkan Stomatological Society, 2020)
Background/Aim: The study aimed to evaluate the quality of life (QOL) of dental students in a private dental school with the use of the WHOQOLBREF scale.